2015
DOI: 10.3389/fendo.2015.00059
|View full text |Cite
|
Sign up to set email alerts
|

Role of IGF1R in Breast Cancer Subtypes, Stemness, and Lineage Differentiation

Abstract: Insulin-like growth factor (IGF) signaling is fundamental for growth and survival. A large body of evidence (laboratory, epidemiological, and clinical) implicates the exploitation of this pathway in cancer. Up to 50% of breast tumors express the activated form of the type 1 insulin-like growth factor receptor (IGF1R). Breast cancers are categorized into subtypes based upon hormone and ERRB2 receptor expression and/or gene expression profiling. Even though IGF1R influences tumorigenic phenotypes and drug resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
119
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(135 citation statements)
references
References 171 publications
7
119
2
Order By: Relevance
“…However, compensation and activating feedback mechanisms collectively depress the efficacy of anti-IGF1R/InsR therapies (11). Only after discerning the dual IGF1R/InsR system dynamics and novel components, will we be able to start to direct patients with suitable tumor subclasses toward more efficient personalized clinical interventions.…”
Section: Discussionmentioning
confidence: 99%
“…However, compensation and activating feedback mechanisms collectively depress the efficacy of anti-IGF1R/InsR therapies (11). Only after discerning the dual IGF1R/InsR system dynamics and novel components, will we be able to start to direct patients with suitable tumor subclasses toward more efficient personalized clinical interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The authors further indicated that IGFIR mRNA extend to be more highly expressed in Luminal A and B subtypes compared with the basal-like and HER2-positive subtypes (173). Many IGFIR inhibitors (mAbs and TKIs) and IGF1/IGF2 neutralizing mABs have been developed and evaluated in clinical trials with some success in early trials but have failed to show benefits in larger phase III trials (174).…”
Section: Other Rtksmentioning
confidence: 96%
“…Analysis of TCGA database indicated that IGFIR is amplified, overexpressed, or somatically mutated in 9% of breast tumors (173). The authors further indicated that IGFIR mRNA extend to be more highly expressed in Luminal A and B subtypes compared with the basal-like and HER2-positive subtypes (173).…”
Section: Other Rtksmentioning
confidence: 99%
“…The results showed overexpression of IGF-1R in EpCAM(+) exosomes of NSCLC patients relative to controls, while no correlation between p-IGF-1R and disease state or IGF-1R levels was found. Given the significant interest in these proteins for cancer diagnosis and treatment, 116118 the pioneering exosome-based analysis performed could be important for establishing IGF-1R and p-IGF-1R as exosomal biomarkers. Although μNMR and nPLEX also performed on-chip detection of intravesicular proteins, such as HSP70, HSP90, and IDH1 R132H, some samples were from cell cultures and off-chip exosome isolation and/or lysis was required.…”
Section: Integrated Microfluidic Platforms For Exosome Analysismentioning
confidence: 99%